High CD44s expression is associated with the EMT expression profile and intrahepatic dissemination of hepatocellular carcinoma after local ablation therapy. Issue 4 (April 2013) - Mima, Kosuke; Hayashi, Hiromitsu; Imai, Katsunori; Kuroki, Hideyuki; Nakagawa, Shigeki; Okabe, Hirohisa; Chikamoto, Akira; Watanabe, Masayuki; Beppu, Toru; Baba, Hideo
Abstract Background/purpose Local ablation therapy (LAT) is a widely used treatment for hepatocellular carcinoma (HCC) because it is less invasive than hepatic resection. The precise molecular mechanism underlying local HCC recurrence after LAT is largely unknown. The CD44 standard isoform (CD44s) is involved in epithelial—mesenchymal transition (EMT) in HCC. We investigate the significance of CD44s expression and EMT expression profile in local HCC recurrence after LAT. Methods We studied the expression levels of CD44s, EMT expression profile (E‐cadherinlow/vimentinhigh expression) and their association with clinicopathological factors in 30 HCC samples from patients with locally recurrent HCCs after LAT following hepatic resection. The alterations of CD44s expression was compared with those in initial HCCs from 150 patients without prior any anticancer treatment including LAT. Results A high CD44s expression was significantly associated with the EMT expression profile (P = 0.002), and it was also detected with a higher frequency in the locally recurrent HCCs after LAT compared to initial HCCs (P < 0.001). In addition, high CD44s expression was associated with the intrahepatic dissemination of HCC after LAT (P = 0.006). Conclusions These results suggest that high CD44s expression is associated with the aggressive recurrence pattern via EMT after LAT for HCC.